2021
DOI: 10.3390/molecules26092401
|View full text |Cite
|
Sign up to set email alerts
|

Pentacyclic Triterpenoids with Nitrogen-Containing Heterocyclic Moiety, Privileged Hybrids in Anticancer Drug Discovery

Abstract: Pentacyclic triterpenoids are well-known phytochemicals with various biological activities commonly found in plants as secondary metabolites. The wide range of biological activities exhibited by triterpenoids has made them the most valuable sources of pharmacological agents. A number of novel triterpenoid derivatives with many skeletal modifications have been developed. The most important modifications are the formation of analogues or derivatives with nitrogen-containing heterocyclic scaffolds. The derivative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 103 publications
(139 reference statements)
0
31
0
Order By: Relevance
“…The introduction of heterocyclic fragments, especially piperazine, has been demonstrated to enhance anticancer properties [ 31 ]. Recently we have found that modification of triterpenoids to indole derivatives on the A-ring with amidation to C28-amide, as well as the introduction of piperazine or N -methyl-piperazine, have a positive effect on anticancer activity [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of heterocyclic fragments, especially piperazine, has been demonstrated to enhance anticancer properties [ 31 ]. Recently we have found that modification of triterpenoids to indole derivatives on the A-ring with amidation to C28-amide, as well as the introduction of piperazine or N -methyl-piperazine, have a positive effect on anticancer activity [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pentacyclic triterpenoids (PTs) are the largest group of natural compounds found in plants. Multiple studies have exhibited that there are a considerable number of PTs revealed significant cytotoxic activity against a variety of cancer cells as well as antitumor efficacy in preclinical animal models [ 5 , 6 , 7 , 8 , 9 ]. They induce their anticancer activity via enhancement of cell apoptosis resulting in suppressing tumor growth.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular hybridization is a commonly molecular modification approach to obtain multiple compounds with therapeutic advantages over the two different drugs [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. The novel hybrid molecules have the potential to enhance efficacy, improve safety, be cost-effective and reduce the propensity to elicit resistance relative to the parent drugs [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%